MANAJEMEN PENANGANAN ANAK DI PENGUNGSIAN KORBAN BENCANA ERUPSI GUNUNG SINABUNG DI PROVINSI SUMATERA UTARA - Pratiwi, Dewinta Sari; Hidayat, Eri Radityawara; Widjaja, Wisnu (Jurnal Manajemen Bencana (JMB), 2019)
Children who survived from natural disasters are not necessarily safe from the threat of life and survival. The emergency condition of the disaster requires the readiness of all humanitarian actors to put forward the principles of protection in the handling of disaster victims especially for vulnerable groups such as children. The eruption of Mount Sinabung is an extraordinary event because it is a disaster with very long evacuation activities and affect the lives of refugee children. This research is a qualitative research with case study approach that aims to analyze the management of the refugee children's handling of disaster victims viewed from the perspective of child protection. The research location was located in Karo Regency with selected participants using purposive and snowball sampling technique. The data was collected through in-depth interviews, observations and document studies assisted by audio-visual materials which were then analyzed by Creswell's data analysis model. The result of this research indicate that child protection factor has not become the point that is considered in the management of the refugee children handling of the eruption of Mount Sinabung eruption as seen from legislative, institutional, planning, organizing, resource management, funding component. Evaluation results of management of refugee children handling are seen from three indicators: the fulfillment of children's rights that only focus on the fulfillment of physical needs; the existence of violations of child protection by the existence of cases or events involving refugee children as perpetrators as well as victims and involvement of children in the demonstration activities and accidents of transportation of school children; as well as other psychosocial mental effects.